2019
DOI: 10.1055/a-1025-0085
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Extracts from Arctium lappa as a Potential Inhibitor for the Activation of Complement System

Abstract: Arctium lappa is a perennial species of the Asteraceae family originally from Europe and Asia. Considered a weed species in the southern region of Brazil, it is popularly used as a natural anti-inflammatory. The complement system is an important component of the innate immune response. However, its exacerbated activation can lead to harmful conditions like autoimmune and inflammatory disorders. Plants that inhibit the activation of complement can be a promising tool in the treatment of inflammatory diseases. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Also, a polysaccharide fraction of A. lappa extracts showed a dose dependent anti‐edematogenic activity and an antinociceptive effect on carrageenan‐induced paw edema in mice . In addition, supercritical extracts from A. lappa leaves were able to inhibit the classical and alternative pathways, as well as the lectin pathway. However, the mechanism involved with the complement modulation needs to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, a polysaccharide fraction of A. lappa extracts showed a dose dependent anti‐edematogenic activity and an antinociceptive effect on carrageenan‐induced paw edema in mice . In addition, supercritical extracts from A. lappa leaves were able to inhibit the classical and alternative pathways, as well as the lectin pathway. However, the mechanism involved with the complement modulation needs to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…The main biologic active compounds shared by the four extracts were lupeol acetate, phytol and α ‐amyrin ( Table ). It is noteworthy that the compounds lupeol acetate and phytol were found in greater proportion among the components of A. lappa extracts that had an inhibitory effect on the activation of the classical and alternative complement pathways . Lupeol acetate, a pharmacologically active triterpenoid, has several potential therapeutic properties such as antiprotozoal, antitumor, cardioprotective, antinociceptive, and anti‐inflammatory activities both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that A. lappa extracts were able to modulate the complement system. [62,63] The complement system is an important part of the immune defense promoting inflammation, phagocytosis, killing of pathogens and acts as a bridge connecting the innate and acquired response. [115] However, the complement can be excessively activated when deregulated, promoting inflammatory and age-related diseases [116] and because of that the system has been considered a therapeutic target for several inflammatory diseases.…”
Section: Modulation Of the Activation Of Complement Systemmentioning
confidence: 99%
“…[115] However, the complement can be excessively activated when deregulated, promoting inflammatory and age-related diseases [116] and because of that the system has been considered a therapeutic target for several inflammatory diseases. [117,118] Fontana et al ( 2019) [62] demonstrated that A. lappa extracts inhibited the activation of both the classical and alternative complement pathways. The terpene compounds, lupeol acetate, amyrin acetate, and diterpene phytol were the main components with described biological action of A. lappa extracts in experiments.…”
Section: Modulation Of the Activation Of Complement Systemmentioning
confidence: 99%